2021
DOI: 10.3389/fnhum.2021.649051
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Cortical and Subcortical Structures in Multiple System Atrophy Patients With Mild Cognitive Impairment

Abstract: ObjectiveThis study aimed to investigate the morphometric alterations in the cortical and subcortical structures in multiple system atrophy (MSA) patients with mild cognitive impairment (MCI), and to explore the association with cognitive deficits.MethodsA total of 45 MSA patients (25 MSA-only, 20 MSA-MCI) and 29 healthy controls were recruited. FreeSurfer software was used to analyze cortical thickness, and voxel-based morphometry was used to analyze the gray matter volumes. Cortical thickness and gray matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Fiorenzato et al ( 2017 ) believed that cortical pathology in MSA‐CI was driven by subcortical degeneration via the frontostriatal circuit. Meanwhile, Cao et al ( 2021 ) proposed that cortical thinning in the left MTG primarily contributed to cognitive deficits in MSA. Our results indicated that cerebellar degeneration and corresponding cortical abnormalities, as well as primary cortical network dysfunction, might simultaneously contribute to MCI in MSA, and early cognitive decline in MSA is more dependent on functional disruptions than on morphological changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiorenzato et al ( 2017 ) believed that cortical pathology in MSA‐CI was driven by subcortical degeneration via the frontostriatal circuit. Meanwhile, Cao et al ( 2021 ) proposed that cortical thinning in the left MTG primarily contributed to cognitive deficits in MSA. Our results indicated that cerebellar degeneration and corresponding cortical abnormalities, as well as primary cortical network dysfunction, might simultaneously contribute to MCI in MSA, and early cognitive decline in MSA is more dependent on functional disruptions than on morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in MSA patients with prominent parkinsonism (MSA‐P), voxel‐based morphometry (VBM) and thickness analysis were combined, and the cognitive dysfunction was shown to be significantly correlated with thinning in the neocortex, cerebellum, and striatum (Kim et al, 2015 ), supporting the concept of subcortical CI. Conversely, Caso et al ( 2020 ) found that, although cortical thinning and subcortical atrophy coexist in MSA‐P patients, CI is related to cortical thinning in temporal regions, indicating primary cortical involvement (Cao et al, 2021 ; Chang et al, 2009 ). However, whether CI in MSA results from primary cortical damage or subcortical degeneration with secondary cortical deafferentation remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, MCI showed hypoperfusion in the IPL, MTG, precuneus, SOG, and MOG. The IPL and MTG are areas where specific cognition is located (Cao et al, 2021 ) and are involved in attention and language processing (Caspers et al, 2013 ; Dong et al, 2021 ). The precuneus is associated with spatial memory (Deconinck et al, 2015 ) and extensively connects cortical and subcortical structures, which plays an important role in the default network (Koch et al, 2018 ; Chen et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study of social defeat stress in mice showed rodents that were victimized had dendritic atrophy ( Fox et al, 2020 ), which can impact regional brain volume. Lastly, studies in aging and diseases showed that changes in brain morphometry can impact cognition ( Cao et al, 2021 , Leong et al, 2017 ). The covariates used in the LMMs above were also used for each portion of the mediation analyses.…”
Section: Methodsmentioning
confidence: 99%